The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1039/b516291b
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the reactions of CH2Br and CH2I radicals with molecular oxygen at atmospheric temperatures

Abstract: The kinetics of the reactions of CH2Br and CH2I radicals with O2 have been studied in direct measurements using a tubular flow reactor coupled to a photoionization mass spectrometer. The radicals have been homogeneously generated by pulsed laser photolysis of appropriate precursors at 193 or 248 nm. Decays of radical concentrations have been monitored in time-resolved measurements to obtain the reaction rate coefficients under pseudo-first-order conditions with the amount of O2 being in large excess over radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
132
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(153 citation statements)
references
References 45 publications
(54 reference statements)
14
132
7
Order By: Relevance
“…The flow reactor with laser photolysis coupled to the resonance gas lamp photoionization mass spectrometer (LP-RPIMS) used in this work has been described previously, 15,16 and only a brief 10 The main photolysis channel leads to C3−C4 bond fission, but in addition other products are formed:…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The flow reactor with laser photolysis coupled to the resonance gas lamp photoionization mass spectrometer (LP-RPIMS) used in this work has been described previously, 15,16 and only a brief 10 The main photolysis channel leads to C3−C4 bond fission, but in addition other products are formed:…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…2,3 Haloalkyl fragments also play a role in atmospheric chemistry as they are generally thought to form peroxy radicals after reacting with O2. 37 As with the CH2I radical, reaction of the CHICl radical with O2 appears to forms a carbonyl oxide or Criegee intermediate in comparably high yield. Pressuredependent measurements of the CH2I + O2 reaction indicate a CH2OO yield of 77% at 15 Torr (the pressure used in the measurement of the ClCHOO absorption cross section), decreasing to around 30% at atmospheric pressure.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…[31][32][33][34][35] Photolysis of CH2I2 in the presence of O2 was first demonstrated by Welz et al 36 to be an efficient route to generate CH2OO in sufficient concentration for kinetics studies at low pressure, following initial work by Eskola et al who had identified I atom formation in the CH2I + O2 reaction. 37 The CH2OO yield in the CH2I + O2 reaction approaches unity at low pressure, decreasing to ~30% at atmospheric pressure. [38][39][40] The UV absorption spectrum of CH2OO has been measured using several spectroscopic techniques.…”
mentioning
confidence: 99%
“…Sunlight can efficiently induce the photolytic decomposition of CH 2 I 2 to form CH 2 I + I; the reaction of CH 2 I + O 2 eventually releases a second I atom; these I atoms might destroy ozone or become transformed to aerosol. 58,59 Even though the reaction of CH 2 I + O 2 has been investigated extensively, [52][53][54][55][56][60][61][62][63][64][65][66] a detailed mechanism of this reaction was established only recently. 67 The proposed mechanisms in the early studies were incomplete because only product channels for the formation of ICH 2 OO and H 2 CO + IO, not CH 2 OO + I, were considered.…”
Section: A Ch 2 I + Omentioning
confidence: 99%